Functional components profile and glycemic index of kidney beans - Xu, Shengshu; Qin, Likang; Mazhar, Muhammad; Zhu, Yong (Frontiers in Nutrition, 2022)
Low glycemic index (GI) diet has been considered as a strategy for type II diabetes patients. In the present study, the phenolics profile, α-amylase inhibitor activities, starch composition as well as the glycemic index of seven varieties of kidney beans were studied. An enzymatic inhibitory reaction model was employed to determine the α-amylase inhibitor activity, and the in vitro digestion model coupled with the 3, 5-dinitrosalicylic acid colourimetry method was adopted to evaluate the starch composition and glycemic index. The results showed that gallic acid was dominant in kidney beans, and the coloured beans contained more phenolics than the white ones. In addition, the α-amylase inhibitor activities of kidney beans ranged from 1.659 ± 0.050 to 4.162 ± 0.049 U/g DW, among which the Y2 variety was the top-ranked. Furthermore, kidney beans starch demonstrated brilliant resistance to digestion with the contribution of resistant starch to total starch between 70.90 ± 0.39 % and 83.12 ± 0.42%. Eventually, these kidney beans were categorised as low GI foods, which ranged from 32.47 ± 0.13 to 52.99 ± 0.56, the resistant starch makes dominant contribution to the low GI. These results indicate that kidney beans can be served as ingredients in functional low GI foods.